Immunophenotypic differences between osteoclasts and macrophage polykaryons: immunohistological distinction and implications for osteoclast ontogeny and function. Issue 12 (December 1990) - Athanasou, N A; Quinn, J
Abstract : The antigenic phenotype of human fetal osteoclasts was compared with that of human tissue macrophages and macrophage polykaryons in foreign body lesions using a large number of monoclonal antibodies directed against myeloid (granulocyte/mononuclear phagocyte) antigens. Osteoclasts expressed a restricted range of macrophage-associated antigens including CD13, CD15A, CD44, CD45, CD54, (ICAM-1), CD71 (transferrin receptor), and CD68. These antigens were also present on macrophages and macrophage polykaryons both of which also strongly expressed CD11a, b, c, CD18, (LFA family), CD14, CD31, CD36, CD37, CD39 and CD43 antigens. There was also weak and occasional expression of CD16 (FcRIII), CD25 (interleukin 2 receptor), CD32 (FcRII), CD35 (C3b receptor) and HLA-DR by macrophage polykaryons. The presence of some macrophage associated antigens on osteoclasts is consistent with their originating from cells of the mononuclear phagocyte system. The numerous differences in antigenic phenotype between osteoclasts and macrophage polykaryons, however, suggest that their pathways of development and differentiation are not identical. The differences discerned in antigenic phenotype should also permit distinction between these polykaryons (and possibly their mononuclear precursors) in normal and diseased tissues.